Blood Transfusion Studies In Sheep and Goat - Banka Pushkar Rajendra; S. Sivaraman; G. Senthil Kumar; P. Balachandran (The Indian Veterinary Journal, 2023)
The present study entitled “Blood transfusion studies in sheep and goats” was conducted for a period of 12 months, from September 2019 to August 2020, with the objectives of studying the shelf life of donor blood and blood transfusion protocol in sheep and goats. Blood was collected in CPDA blood bags (@10-15ml/kg body weight) from 10 apparently healthy sheep and goat donors. Anaemia was diagnosed based on clinical examination and haemato-biochemical studies. Blood transfusion was carried out (with stored blood) in 6 sheep and 9 goats (@ 10-15ml/kg body weight) post cross matching. Haemato-biochemical studies showed significant increase in Hb, PCV and total protein values in sheep and significant increase in Hb, PCV, RBC, WBC and eosinophils in goats after blood transfusion. In the present study, blood transfusion carried out was successful in all cases without any adverse reactions.